2023
DOI: 10.1111/jgh.16384
|View full text |Cite
|
Sign up to set email alerts
|

Re‐intervention rates and symptom‐free survival at 1 year after endoscopic versus surgical management of strictures in Crohn's disease: A propensity matched analysis of a prospective inflammatory bowel disease cohort

Partha Pal,
Jaini Gala,
Pradeep Rebala
et al.

Abstract: Background and AimResection for Crohn's disease (CD) related strictures is definitive but carries risk of morbidity, recurrence, and short bowel syndrome. On the contrary, the durability of endotherapy (ET) for CD‐related strictures is questionable. Prospective comparative studies are limited. We aimed to prospectively compare the outcomes of ET in CD strictures with a case‐matched surgical therapy (ST) cohort.MethodsPatients undergoing ET or resection for primary CD strictures (symptomatic, non‐traversable, &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“… 73 Both mechanical dilation and EBD have shown similar safety profiles and effectiveness for ileoanal and rectal strictures following ileal pouch‐anal anastomosis (IPAA), with no significant difference in complications. 79 Balloon‐assisted enteroscopy‐based endoscopic stricturotomy (BAE‐based ES) has also been found to be effective and safe for deep small bowel strictures. 75 With ongoing advancements in endoscopic techniques, there is great potential for further improvements in safety, effectiveness, and patient outcomes.…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“… 73 Both mechanical dilation and EBD have shown similar safety profiles and effectiveness for ileoanal and rectal strictures following ileal pouch‐anal anastomosis (IPAA), with no significant difference in complications. 79 Balloon‐assisted enteroscopy‐based endoscopic stricturotomy (BAE‐based ES) has also been found to be effective and safe for deep small bowel strictures. 75 With ongoing advancements in endoscopic techniques, there is great potential for further improvements in safety, effectiveness, and patient outcomes.…”
Section: Managementmentioning
confidence: 99%
“…If, resection is needed, minimizing the interval between diagnosis and surgery is important to reduce postoperative complications. 79 The LIR!C trial provided evidence that early surgery, defined as resection for luminal involvement without prior surgeries, is not only a viable alternative to biologics but also reduces costs significantly. 77 …”
Section: Managementmentioning
confidence: 99%
“…Although the risk of first intestinal surgery (33.3% at 5 years and 46.6% at 10 years) is decreasing with current medical therapy, the rate of second surgery has not decreased in the last 3 decades [ 5 , 6 ]. Hence, IIBD is an alternative, effective option to surgery which should be discussed with patients albeit with a higher risk of recurrence and mild risk of complications [ 7 ]. IIBD can also be helpful to delay up to 6.5 years as shown in a retrospective study [ 8 ].…”
Section: Understanding the Natural History Of Ibd And Indications Of ...mentioning
confidence: 99%
“…A recent prospective, propensity-matched analysis of CD strictures (<5 cm, ≤3 in number) with 1-year follow-up showed that the cumulative probability of symptoms recurrence/treatment escalation/re-surgery was not different between those who underwent EBD and those who underwent surgery. However, the rate of re-intervention was higher in the EBD group [ 7 ].…”
Section: Endoscopic Balloon Dilationmentioning
confidence: 99%